From Vico to the sociocultural imagination. (June 2015) - Zittoun, Tania
The papers by Mariagrazia Granatella (2015), Tuuli Pern (2015) and Pablo Rojas (2015), invited by Tateo (2015) engage in a dialogue with the texts of Giambattisto Vico, a philosopher from the 18th century. In this commentary, focusing on imagination, I first follow the authors' effort to show the compatibility between Vico's ideas and current cultural psychology; I then highlight two issues of particular interest emerging from this dialogue.